Mechanisms of Skin Toxicity Associated with Metabotropic Glutamate Receptor 5 Negative Allosteric Modulators. Issue 7 (20th July 2017) - Shah, Falgun; Stepan, Antonia F.; O'Mahony, Alison; Velichko, Sharlene; Folias, Alexandra E.; Houle, Christopher; Shaffer, Christopher L.; Marcek, John; Whritenour, Jessica; Stanton, Robert; Berg, Ellen L.
Summary: Cutaneous reactions represent one of the most common adverse drug effects observed in clinical trials leading to substantial compound attrition. Three negative allosteric modulators (NAMs) of metabotropic glutamate receptors (mGluRs), which represent an important target for neurological diseases, developed by Pfizer, were recently failed in preclinical development due to delayed type IV skin hypersensitivity observed in non-human primates (NHPs). Here we employed large-scale phenotypic profiling in standardized panels of human primary cell/co-culture systems to characterize the skin toxicity mechanism(s) of mGluR5 NAMs from two different series. Investigation of a database of chemicals tested in these systems and transcriptional profiling suggested that the mechanism of toxicity may involve modulation of nuclear receptor targets RAR/RXR, and/or VDR with AhR antagonism. The studies reported here demonstrate how phenotypic profiling of preclinical drug candidates using human primary cells can provide insights into the mechanisms of toxicity and inform early drug discovery and development campaigns. Graphical Abstract: Highlights: mGluR5 NAMs with skin hypersensitivity were profiled in primary human cells 5, 6 showed irritation and immunomodulatory activities in these co-culture models Phenotypic profiling in primary human cells complemented transcriptional profiling PGE2 increase and AhR decrease as potential mechanisms of skin hypersensitivity Abstract : Shah et al. show that phenotypic profiling in standardized panels of primary human cell/co-culture systems can enable identification of likely mechanisms of skin hypersensitivity to mGluR5 negative allosteric modulators (NAMs), observed in vivo.